The health care dilemma a comparison of health care systems in three European countries and the US - Elizabeth G. Armstrong; Fischer, Martin R.; Parsa-Parsi, Ramin W.; Wetzel, Miriam (World Scientific Publishing Co.Pte.Ltd., 2011)
n an age of spiraling costs, it is no surprise that health care policy and health care systems are now among the most hotly debated and controversial topics in many countries of the world today. The issue is literally one of life-and-death, and affects millions across the globe as they struggle to answer the question of who pays for their health care. This book explores the health care systems of Denmark, Germany, and Sweden, and compares them with the system in the United States through 30 first-hand case reports by advanced medical students taking part in an international exchange program